Pengaruh Pembinaan Koni Terhadap Prestasi Atlet di Kabupaten Garut - Sartibi Bin Hasyim; Lia Juliasih; Gesti Fransiska (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
The background of the problem of this study departs from the findings of the author regarding the decline in the achievements of athletes in Garut Regency, especially in the period 2014-2018. This phenomenon is allegedly caused by, among others, the inadequate coaching conducted by KONI in Garut Regency. The purpose of this study was to determine the effect of KONI coaching on the achievements of athletes in Garut Regency. The method used is a descriptive writing method with a quantitative approach. The population of the research was 294 athletes who were coached by KONI Garut Regency, based on Slovin's calculation, the number of samples was 75 people. The sampling technique used is probability sampling with a random sampling method. Data collection techniques used were questionnaire, observation, interview and documentation study. The analysis technique used was a simple linear regression analysis technique using calculations using SPSS software. From the results of the analysis note that each variable is considered good by the respondent, but there are aspects that need to be improved. On the Guiding variable there are a number of findings including low socialization of goals and coaching methods to athletes, poorly documented achievement records, lack of facility provision, incentive issues, lack of evaluation and corrective actions due to HR and management management that are not optimal. On the athlete performance variable, the problem lies in providing incentives and the quantity of training that is not optimal, this is due to the limited budget of the KONI. Based on the results of statistical calculations, the tcount is 4,656 and the table is 1,99. So the proposed hypothesis can be accepted, meaning that there is an influence of KONI coaching on athletes' achievements in Garut Regency. The magnitude of the influence or determinant coefficient of 0.229, meaning that the influence of KONI coaching on athletes' achievements by 22.9%.